Radiation Exposure of Patients in Comprehensive Computed Tomography of the Head in Acute Stroke - Cohnen, M.; Wittsack, H.-J.; Assadi, S.; Muskalla, K.; Ringelstein, A.; Poll, L.W.; Saleh, A.; Mödder, U. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: To assess patient radiation exposure in comprehensive stroke imaging using multidetector row CT (MDCT) combining standard CT of the head, cerebral perfusion (CTP), and CT angiography (CTA) studies.METHODS: Examination protocols for CT and CTA of cerebral and cervical vessels, as well as CTP were simulated using a Somatom Sensation Cardiac 64. Effective doses were derived from measurements with the use of lithium-fluoride thermoluminescent dosimeters (LiF-TLD) at several organ sites using an Alderson-Rando phantom.RESULTS: LiF-TLD measurements resulted in effective doses of 1.7 mSv for CT, 1.9 mSv for CTA of intracranial vessels, and 2.8 mSv for CTA of cervical vessels, respectively. Depending on examination parameters, effective doses varied between 1.1 and 5.0 mSv for cerebral CTP. For CTP, local doses in the area of the primary beam ranged between 114 and 444 mGy.CONCLUSIONS: Comprehensive stroke imaging may result in up to 9.5 mSv with possible local doses of 490 mGy. Although critical doses for organ damage (eg, cataract formation or hair loss) are not reached, physicians need to be aware of possible radiation induced sequelae particularly in repetitive examinations.